PERSEPSI PERAWAT TENTANG KEBUTUHAN SPIRITUAL DI RUANG ICU RSUD DR. TJITROWARDOJO PURWOREJO - Mugihartadi (Jurnal Ilmiah Keperawatan, 2021)
Background: The basic needs of the patient include physical, psychological, social and spiritual needs. Spiritual needs are provided to patients in the ICU through spiritual care services. Spiritual care is a practice and procedure performed by nurses on patients to fulfill the patient's spiritual needs through prayer, prayer, dhikr etc. Purpose: This study aims to explore nurses' perceptions of patients' spiritual needs. Method: The method used in this research is to use qualitative descriptive exploration. Results: Qualitative data analysis using NVivo Plus Twelve resulted theme is the patient's spiritual needs, consisting of two categories, namely giving and fulfillment. Conclusion: Spiritual needs are basic needs needed by patients in the ICU